Sidik Jari DNA dan Fenotipe pada Populasi Kambing Gembrong dengan Status Kritis di Karangasem, Bali (DNA FINGERPRINT AND PHENOTYPE ON THE CRITICAL POPULATION STATUS OF GEMBRONG GOAT IN KARANGASEM REGENCY, BALI) - Zein, Moch Syamsul Arifin; Sulandari, Sri (Jurnal Veteriner, 2014)
Gembrong goat is animal genetic resources which endemic in Bali island and only exists in Karangasemregency. The current population status of the gembrong goat is critical. Therefore, the population developmentof in-situ or ex-situ needs to be conducted. Close relative mating tend to occur in conditions such as in asmall population, critical status or limited distribution. Low degree of genetic variability is often found insuch conditions. Mating arrangements based on DNA data of fingerprint was developed in this study toavoid mating between close relatives (inbreeding). Pedigree detection was analyzed using fifteen (15)microsatellite markers as recommended by ISAP/FAO. The results showed that polymorphic alleles foundin the microsatellite markers of SRCRSP3, ILSTS005, MCM527 (4 alleles), followed BM1818 (3 alleles),and ILSTS029, BMS1494, MAF035, OARFCB20, OARE54, MAF70, ILSTS11, ETH10 (2 alleles).Monomorphic allele (1 allele) was also found in microsatellite markers of SPS113, CSRD247, INRA0132.DNA fingerprint of the gembrong goat population was created by genetic distance between individuals,and indicated six clades / haplogroups. It is suggested from this study that mating arrangements betweendifferent clades should be applied to increase genetic diversity. Description of morphologies such as haircolor and body size, were used as basic considerations in determining the authenticity of gembrong goat.Among the population of gembrong goat in this study, hair color of the goat showed white (78.95%), amixture of light brown and white (15.79%), and a mixture of brown and black (5.26%). Gembrong goat bodysize in this study was still in the range of the previous studies. The analysis results of DNA fingerprintsand phenotypes can be used as a basis for rescue and development of gembrong goats, in an attempt toform a large gene pool with high viability for the conservation, development and sustainable uses.
Keywords: gembrong goat, critical status, DNA fingerprint, clade/haplogroup, fenotype